2020
DOI: 10.1002/path.5451
|View full text |Cite
|
Sign up to set email alerts
|

FDXR regulates TP73 tumor suppressor via IRP2 to modulate aging and tumor suppression

Abstract: Ferredoxin reductase (FDXR) is a mitochondrial flavoprotein that initiates electron transport from NADPH to several cytochromes P450 via two electron carriers, ferredoxin 1 (FDX1) and FDX2. FDXR is the sole ferredoxin reductase in humans and plays a critical role in steroidogenesis and biosynthesis of heme and iron–sulfur clusters. However, much less is known about the role of FDXR in cancer. Here, we show that FDXR plays a role in tumorigenesis by modulating expression of the tumor suppressor p73. By using ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Interestingly, p53 is known to play a pivotal role in controlling iron homeostasis by direct interaction with Ferredoxin Reductase (FDXR) and Iron Responsive Element Binding Protein 2 (IRP2) proteins [ 20 , 21 , 22 ]. Additionally, iron depletion triggered p53 phosphorylation and stabilization, thus preventing its proteasomal degradation [ 23 , 24 , 25 , 26 ]. Recently, Shen and colleagues demonstrated that intracellular iron overload shortens p53 half-life by promoting p53 nuclear export and cytosolic degradation [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, p53 is known to play a pivotal role in controlling iron homeostasis by direct interaction with Ferredoxin Reductase (FDXR) and Iron Responsive Element Binding Protein 2 (IRP2) proteins [ 20 , 21 , 22 ]. Additionally, iron depletion triggered p53 phosphorylation and stabilization, thus preventing its proteasomal degradation [ 23 , 24 , 25 , 26 ]. Recently, Shen and colleagues demonstrated that intracellular iron overload shortens p53 half-life by promoting p53 nuclear export and cytosolic degradation [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we and others showed that p73-deficient mice are prone to spontaneous tumors along with chronic inflammation in multiple organs [ 4 , 21 ]. Interestingly, mice deficient in Rbm38 are also prone to spontaneous tumors with defects in immune system and have a short lifespan [ 22 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…For Rbm38 −/− mice, 7 of them were generated for this study and 23 of them were generated previously [ 22 ]. For Trp73 +/− mice, 4 of them were generated for this study and 28 were generated previously [ 21 ]. All the mice were derived from the same C57BL/6 background and maintained in the same animal facility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining candidates identified by haplotype trend regression may be broadly categorized in terms of known involvement in cancer, metastasis, and age-of-onset in disease. AGO2 (argonaute 2), CNNM1 (cyclin and CBS domain divalent metal cation transport mediator 1), KIAA1109 , and TP73 (tumor promoter 73) have been implicated in breast cancer, metastasis, and disease age-of-onset ( 49-57 ). The noncoding LINC00941 RNA, LYPD6B (LY6/PLAUR Domain Containing 6B), and PPFIBP1 (liprin-beta-1) have been implicated in cancers that may or may not include breast cancer, have been implicated in metastasis, but have no known association with disease age-of-onset ( 58-61 ).…”
Section: Discussionmentioning
confidence: 99%